(untitled) (Research, Society and Development, 2022)
Cheese and dulce de leche are products prone to microbial contamination, deterioration generates undesirable sensory aspects making the product unacceptable for consumption. Consequently, product waste and economic loss occur, in addition to causing damage to consumer health. There are several alternatives to reduce microbial contamination, but the current consumer trend for natural products has tended to introduce these in place of synthetic compounds. One of the ingredients that can possibly be a substitute for chemical preservatives is coconut oil due to its composition lauric acid, a fungicidal substance. The objective of this work was to evaluate its action potential as an antifungal agent in dairy products. The method of diffusion in agar and minimum inhibitory concentration was applied to evaluate the activity of coconut oil on Penicillium roquefort. Some studies have demonstrated the activity of coconut oil against Candida spp., Saprolegnia parasitic, Colletotrichum gloesporioides and Aspergillus fumigatus species. However, coconut oil was not able to inhibit the growth of Penicillium roquefort in the concentrations that could be used in the dairy products described in the work.